Nodal degeneracy of guided modes in uniaxial crystal slabs - Pan, Xinyang; Li, Haitao; Dong, Weijie; Zhou, Xiaoxi; Xing, Ke-Ao; Hu, Chuandeng; Wang, Gang; Hou, Bo (Frontiers in Physics, 2023)
We study the dispersions of the guided modes in the continuous uniaxial crystal slab waveguide and engineer their degeneracies through dielectric anisotropy. By switching the uniaxial positivity and negativity, we can obtain distinctive nodal types, point and line, for the lowest degeneracy in frequency. The mirror symmetry protection is pointed out, and the degeneracy properties are intuitively analyzed through comparing the approximate slopes of the guided modes. Our results reveal a link between the lowest nodal types and the positivity/negativity of the uniaxial dielectric tensor, and provide a new approach to regulate the topology of degeneracy in two-dimensional photonic bands.